The Impact of Visitor Experience on Community Loyalty in Borneo Convention Centre Kuching - Mohammad Amirul Ayu, Rajiman; Shaik Azahar, Shaik Hussain; Ahmad Hazizi, Shah Jamil (Springer, Cham, 2024)
This study aims to analyze the customer engagement and value-proposition in influencing the visitor experience to ensure they will become a loyal visitor. The study focuses on the visitor experience at Borneo Convention Center Kuching (BCCK). The researcher uses quantitative methods by distributing as many as 384 questionnaires to individuals in Sarawak who have visited BCCK. The results of this questionnaire form can help collect data to analyze using SPSS to meet the needs of the study. With this study, the researcher can know whether these factors influence visitors’ overall experiences. Additionally, it can also help parties involved with the management of BCCK, especially in developing the Customer Experience framework, to improve their visitor totality of cognitive, affective, sensory, and behavioral consumer responses during all stages of the consumption process, including pre-purchase, consumption, and post-purchase stages for the services provided by BCCK.